The Nature of the Obligation to Preserve the Goods in the Contract for the International Sale of Goods - Mohammed, Zahraa Raad; Hussein, Akram Mohammed (Journal of Ecohumanism, 2024)
International laws and agreements stipulate the obligations of the seller in the international sales contract at times and the obligations of the buyer at other times, but they do not mention among these obligations specified in their texts the joint obligations imposed on the two parties according to the Circumstances, which is the obligation to preserve the goods, as we find that they were stipulated independently in the texts of articles It is independent of the specific obligations of each of them, and the legal nature of this obligation has not been clarified. Therefore, in this research we will discuss the nature of the obligation to preserve the goods as a joint obligation on both the seller at times and the buyer at other times. Objectives: The study aims to clarify the legal nature of the obligation to preserve goods, as this obligation is based on the fact that the person who has the goods in his possession or at his disposal is obligated to preserve them and protect them from destruction and damage . It is necessary to clarify the legal nature of such an obligation, and determine whether it is an obligation to achieve A goal or a commitment to exercise care, and if it is a commitment to exercise care, what is the amount of care required? Methodology: The study was adopted to clarify the position of laws and agreements on this obligation in terms of stating the position of the Vienna Convention on the International Sale of Goods of 1980, as well as the Hague Convention of 1964, the principles of the European Contract , the American Trade Law, and the English Sale of Goods Law, in addition to stating the position of the Iraqi legislator on this obligation. Results:The result of the research is summarized in explaining the concept of the obligation to preserve goods in the international sales contract by stating its definition in the laws and agreements regulating it, in addition to explaining the discussions that were held at the Vienna Convention conference and how to organize the text of the obligation to preserve, and explaining the result from the nature of this obligation: is it The person obligated to preserve is obligated to achieve a result, and if he does not do so, he is considered in breach, or is his obligation limited to exercising only the necessary diligence, and what is the extent of this diligence? Conclusion: The subject goods to the obligation to preserve require the person obligated to preserve them to take the necessary measures on them for the purpose of preserving them according to what is consistent with their nature and the procedures they require for the purpose of preserving them in a way that protects them from destruction or damage to which they may be exposed.